Preparation and application of two-dimensional carbon matrix sheet embedded monodisperse bismuth nanoparticle composite material

By synthesizing a two-dimensional carbon matrix sheet-embedded bismuth nanosphere composite material based on nanopore capillary force, the problems of Bi nanoscale, large current density stability and low carbon coating efficiency in Bi/C composite materials were solved, and the problem of Bi nanoscale, high current density stability and low carbon coating efficiency in Bi/C composite materials was achieved. Lithium, sodium and potassium ion battery negative electrode materials with high capacity, long cycle life and excellent rate performance.

CN119133382AActive Publication Date: 2024-12-13SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411062331.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2024-12-13
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

The energy storage performance of existing Bi/C composite materials in lithium, sodium and potassium ion batteries is limited by the large size of Bi nanometers, insufficient content and low carbon coating efficiency, making it difficult to cyclize stably for a long time under high current density, which cannot be met. Ultra-high capacity and rate performance requirements.

Method used

Using a method based on the force of nanopore capillary force, a two-dimensional carbon matrix sheet-embedded monodispersed bismuth nanosphere composite material is synthesized by liquid reduction method to achieve ultra-small size, ultra-high content and high efficiency carbon coating of Bi, and ultra-thin, Stable two-dimensional carbon matrix sheets embedded in bismuth nanosphere composites.

Benefits of technology

It realizes high specific capacity, long cycle life and excellent rate performance of lithium, sodium and potassium ion battery negative electrode materials, can provide high capacity output at high current density, and maintain stable capacity during long cycles, significantly improving the Bi base Electrochemical properties of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133382A_ABST
    Figure CN119133382A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery negative electrode materials, and discloses preparation and application of a two-dimensional carbon matrix sheet embedded monodisperse bismuth nanoparticle composite material. The preparation method comprises the following steps: treating a bismuth precursor by a liquid reduction method to obtain porous elemental bismuth; then dispersing porous elemental bismuth into a system containing a carbon matrix precursor to form a uniform and stable dispersion liquid, and freeze-drying to obtain mixed aerogel; and calcining the mixed aerogel in a protective atmosphere to obtain the two-dimensional carbon matrix sheet embedded monodisperse bismuth nanosphere composite material. The method is simple in process, low in raw material cost, high in controllability of operation steps and capable of realizing large-scale production. The obtained product is novel in structure, the bismuth nanospheres embedded by the two-dimensional carbon substrate sheet are small in particle and uniformly dispersed, and the reaction activity is high; when being used as a negative electrode material of a lithium ion battery and / or a sodium ion battery and / or a potassium ion battery, the composite material has the characteristics of high specific capacity, long cycle life and excellent rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery negative electrode materials, and particularly relates to the preparation and application of a two-dimensional carbon matrix sheet embedded monodisperse bismuth nanoparticle composite material. Background Art

[0002] Bismuth (Bi) is a representative alloy material with a suitable redox potential (Bi 3+ / Bi=0.308V vs.SHE), lower thermal conductivity, high electrical conductivity (7.8×10 5 S m -1 )Higher theoretical specific capacity (385mAh g -1 ) and volume energy density (3800mAh cm -3 ) has the advantages of volume capacity exceeding any negative electrode material reported so far. Moreover, Bi belongs to the hexagonal crystal system, and the large interlayer spacing along the c-axis (d(003)=0.395nm) is conducive to the diffusion of Li, Na, and K ions. These comprehensive advantages make metallic Bi-based materials a very promising negative electrode material for lithium, sodium, and potassium ion batteries. However, during the charge and discharge process, Bi has obvious structural changes. For example, it has a volume expansion rate of 250% in the fully sodium-embedded state and a volume expansion rate of 409% in the fully potassium-embedded state. This will cause the structure of the Bi-based material to break or even shatter, and lose its electrochemical activity. Constructing a composite material of nanostructured Bi with a carbon matrix is ​​currently the most commonly used method to improve the lithium, sodium, and potassium storage performance of Bi-based materials.

[0003] Although some positive progress has been made in the construction of Bi / C composite materials in improving the storage performance of sodium and potassium (Journal of Alloys and Compounds, 2023, 935: 168207. Small, 2022, 18 (44): 2204045), the storage performance of Bi-based materials for lithium, sodium and potassium needs to be further improved, because lithium, sodium and potassium ion batteries are / will be used as high-power energy storage devices in fields such as energy storage power stations, smart grids, and electric vehicles. This requires lithium, sodium and potassium ion batteries to be used at ultra-high current densities (such as 10Ag -1) for a long time and stably cycle under high capacity. The lithium, sodium and potassium storage performance of Bi / C composites is mainly limited by the low Bi content in the material, which cannot exert high capacity performance, and the large Bi size cannot obtain faster electrochemical reaction kinetics to improve rate performance. Therefore, how to continue to reduce the nanosize of Bi (~10nm) in Bi / C composites, further increase the Bi content (>90wt%), and ensure effective carbon coating is an important issue to improve the sodium and potassium storage performance of Bi-based materials. The currently reported synthesis methods of nanomaterials cannot simultaneously meet the requirements of ultra-small size, ultra-high content and efficient carbon coating of Bi in Bi / C composites. It is necessary to develop new nanomaterial synthesis methods to meet the above structural requirements at the same time, in order to further improve the lithium, sodium and potassium storage performance of Bi-based materials. Summary of the invention

[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a composite material of two-dimensional carbon matrix sheets embedded with monodisperse bismuth nanoparticles.

[0005] The invention adopts a new synthesis method of nanomaterials based on the action of nanopore capillary force to synthesize a composite material of two-dimensional carbon matrix sheets embedding monodisperse bismuth nanospheres.

[0006] Another object of the present invention is to provide a two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanoparticle composite material prepared by the above method.

[0007] Another object of the present invention is to provide the use of the above-mentioned two-dimensional carbon matrix sheet embedded monodisperse bismuth nanoparticle composite material in ion batteries.

[0008] The two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material prepared by the present invention has the characteristics of high specific capacity, long cycle life and excellent rate performance when used as negative electrode material for lithium ion batteries and / or sodium ion batteries and / or potassium ion batteries.

[0009] The purpose of the present invention is achieved through the following solutions:

[0010] A method for preparing a composite material of two-dimensional carbon matrix sheets embedded with monodisperse bismuth nanoparticles comprises the following steps:

[0011] (1) The bismuth precursor is treated by a liquid reduction method to obtain porous elemental bismuth;

[0012] (2) dispersing the porous elemental bismuth obtained in step (1) into a system containing a carbon matrix precursor to form a uniform and stable dispersion, and freeze-drying to obtain a hybrid aerogel;

[0013] (3) calcining the mixed aerogel obtained in step (2) under a protective atmosphere to obtain a two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material.

[0014] The bismuth precursor in step (1) is at least one of bismuth oxide, bismuth sulfide, bismuth selenide, bismuth oxybromide, bismuth oxychloride, bismuth oxyiodine, bismuth oxycarbonate, and bismuth selenium oxide.

[0015] The reducing agent used in the liquid reduction method in step (1) is one of hydrazine hydrate, sodium borohydride and ascorbic acid.

[0016] The molar ratio of the bismuth precursor to the reducing agent in step (1) is 0.1-2.5:1.

[0017] The liquid in the liquid reduction method of step (1) is at least one of water, ethanol and methanol; wherein the ratio of the liquid to the reducing agent is 30-250 mL: 1-10 mmol.

[0018] The carbon matrix precursor in step (2) is at least one of graphene, two-dimensional transition metal carbide (MXene) and its derivatives, ammonium citrate, citric acid, chitosan, tartaric acid, gum arabic, cellulose and its derivatives.

[0019] In step (2), the mass ratio of the porous elemental bismuth to the carbon matrix precursor is 0.05-10:0.01-5.

[0020] The ratio of the solvent to the carbon matrix precursor in the dispersion of step (2) is 20-200 mL: 0.01-5 g.

[0021] Before freeze drying in step (2), the dispersion is rapidly cooled by liquid nitrogen.

[0022] The protective atmosphere in step (3) is at least one of argon and nitrogen.

[0023] The heating rate of the calcination in step (3) is 1-20°C / min; the calcination temperature is 300-1000°C, and the calcination holding time is 0.5-5h.

[0024] The two-dimensional carbon matrix sheet prepared by the above method embeds the monodisperse bismuth nanoparticle composite material.

[0025] The above-mentioned two-dimensional carbon matrix sheet embedded monodisperse bismuth nanoparticle composite material is used in ion batteries.

[0026] The ion battery includes one of a lithium ion battery, a sodium ion battery, and a potassium ion battery.

[0027] The two-dimensional carbon matrix sheet embedded monodisperse bismuth nanoparticle composite material is used as a negative electrode material in an ion battery, comprising the following steps:

[0028] A two-dimensional carbon matrix sheet is embedded with a monodisperse bismuth nanosphere composite material, carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, mixed to make a slurry, and then coated on a copper foil to obtain an ion battery negative electrode material.

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0030] (1) The present invention provides a new method for synthesizing nanomaterials based on nanopore capillary forces to synthesize a two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material, which can simultaneously achieve the requirements of ultra-small size, ultra-high content, efficient carbon coating, and adjustable Bi content in the bismuth / carbon composite material. The ultrafine Bi nanospheres in the two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material prepared by the present invention are completely embedded by the two-dimensional ultra-thin oxygen-rich nitrogen-doped carbon sheet. This overall two-dimensional ultra-thin and stable structure shortens the path of lithium, sodium, and potassium ions passing through the two-dimensional plane during the charging and discharging process, ensuring ultra-fast transmission of electrons / ions and extremely fast electrochemical reaction kinetics. The ultra-small Bi nanospheres are also conducive to reducing volume stress during the expansion process.

[0031] (2) The equipment required by the present invention is simple, easy and safe to operate, and has low cost and can be mass-produced.

[0032] (3) The composite material of two-dimensional carbon matrix sheet embedded with monodisperse bismuth nanoparticles prepared by the present invention has a novel structure. The bismuth nanospheres embedded in the two-dimensional carbon matrix sheet are small and evenly dispersed, and have high reaction activity. When used as negative electrode materials for lithium ion batteries and / or sodium ion batteries and / or potassium ion batteries, it has the characteristics of high specific capacity, long cycle life and excellent rate performance: when applied to the negative electrode of sodium ion batteries, at 50Ag -1 The ultra-high current density provides 397.8 mAh g -1 Ultra-high capacity output at 10Ag -1 Under the condition of high current density, after 1600 long cycles, it still maintained 467.3mAh g -1 When applied to the negative electrode of potassium ion batteries, at 50Ag -1 The high current density provides 275.8 mAh g -1 High capacity output at 10Ag -1 After 1200 long cycles under high current density conditions, it still maintained 330.8 mAh g -1 Excellent capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The X-ray diffraction pattern (a) and transmission electron microscopy patterns (b)-(d) of the porous elemental bismuth obtained in Example 1.

[0034] Figure 2 The X-ray diffraction pattern (a), Raman pattern (b), and thermogravimetric curve (c) of the two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material obtained in Example 1 are shown.

[0035] Figure 3 Transmission electron microscopy images (a)-(d) of the two-dimensional carbon matrix sheet embedded monodisperse bismuth nanosphere composite material obtained in Example 1; atomic force microscopy images and corresponding height curves (e)-(f); high-resolution transmission electron microscopy image (g); element distribution diagrams (h)-(l).

[0036] Figure 4 This is the particle size distribution diagram of the Bi nanospheres of the two-dimensional carbon matrix sheet embedded monodisperse bismuth nanosphere composite material obtained in Example 1.

[0037] Figure 5 This is a diagram showing the storage performance of the two-dimensional carbon matrix sheet embedded with monodisperse bismuth nanosphere composite material obtained in Example 1.

[0038] Figure 6 This is a graph showing the potassium storage performance of the two-dimensional carbon matrix sheet embedded monodisperse bismuth nanosphere composite material obtained in Example 1. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0040] Unless otherwise specified, the reagents used in the examples can be purchased from the market.

[0041] Example 1

[0042] (1) Take 0.5 g of iodine bismuth oxide and ultrasonically disperse it in 50 mL of water to form a uniform dispersion. During the stirring process, 10 mL of 0.1 mol / L hydrazine hydrate solution is slowly added to the dispersion and stirred for 30 minutes. After filtering, washing and drying, a porous elemental bismuth is obtained.

[0043] (2) 0.3 g of the porous elemental bismuth synthesized in step (1) was uniformly dispersed in 50 mL of water, and then 0.05 g of graphene and 0.05 g of chitosan were added, and a uniform and stable dispersion was formed after vigorous stirring for 1 h. After rapid cooling with liquid nitrogen and freeze drying for 40 hours, a mixed aerogel was obtained.

[0044] (3) placing the mixed aerogel obtained in step (2) in a tubular furnace, heating it at a rate of 1°C / min under an argon atmosphere, and keeping it at 500°C for 3 h to obtain a two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material.

[0045] Example 2

[0046] (1) Take 0.2 g of bismuth oxychloride and 0.5 g of bismuth selenide oxide (Nanotechnology 2021, 32, 485602) and ultrasonically disperse them in 100 mL of ethanol to form a uniform dispersion. During the stirring process, 15 mL of 0.1 mol / L sodium borohydride solution is slowly added to the above dispersion and stirred for 30 min. After filtering, washing, and drying, a porous elemental bismuth is obtained.

[0047] (2) 0.3 g of the porous elemental bismuth synthesized in step (1) was uniformly dispersed in 50 mL of water, and then 0.1 g of gum arabic and 0.1 g of chitosan were added, and stirred vigorously for 1 h to form a uniform and stable dispersion. After rapid cooling with liquid nitrogen and freeze drying for 40 hours, a hybrid aerogel was obtained.

[0048] (3) placing the mixed aerogel obtained in step (2) in a tubular furnace, heating it at a rate of 5°C / min under an argon atmosphere, and keeping it at 700°C for 5 hours to obtain a two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material.

[0049] Example 3

[0050] (1) Take 0.5 g of bismuth oxychloride and ultrasonically disperse it in 200 mL of methanol to form a uniform dispersion. During the stirring process, slowly add 30 mL of 0.1 mol / L sodium borohydride solution to the dispersion and continue stirring for 30 minutes. After filtering, washing, and drying, a porous elemental bismuth is obtained.

[0051] (2) 0.5 g of the porous elemental bismuth synthesized in step (1) was uniformly dispersed in 100 mL of water, and then 0.4 g of the two-dimensional Ti3C2 material and 0.1 g of chitosan were added, and a uniform and stable dispersion was formed after vigorous stirring for 1 h. After rapid cooling with liquid nitrogen and freeze drying for 40 hours, a hybrid aerogel was obtained.

[0052] (3) placing the mixed aerogel obtained in step (2) in a tubular furnace, heating it at a rate of 3°C / min under an argon atmosphere, and keeping it at 900°C for 2 hours to obtain a two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material.

[0053] Example 4

[0054] (1) Take 3.0 g of bismuth selenide and 2.0 g of bismuth oxybromide, and ultrasonically disperse them in 200 mL of water to form a uniform dispersion. During the stirring process, 50 mL of 0.1 mol / L ascorbic acid solution is slowly added to the dispersion, and stirring is continued for 30 minutes. After filtering, washing, and drying, a porous elemental bismuth is obtained.

[0055] (2) 4.0 g of the porous elemental bismuth synthesized in step (1) was uniformly dispersed in 200 mL of water, and then 1.0 g of tartaric acid was added and stirred vigorously for 1 h to form a uniform and stable dispersion. After rapid cooling with liquid nitrogen and freeze drying for 40 hours, a hybrid aerogel was obtained.

[0056] (3) placing the mixed aerogel obtained in step (2) in a tubular furnace, heating it at a rate of 7°C / min under an argon atmosphere, and keeping it at 1000°C for 2 h to obtain a two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material.

[0057] Test Example:

[0058] The two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite materials prepared in Examples 1-4 were respectively mixed with PVDF and carbon black in a mass ratio of 8:1:1, ground and transferred into a small glass bottle, N-methylpyrrolidone (NMP) was added, and magnetic stirring was performed for 1 hour. The material was coated on a copper foil to make an electrode, and a button battery was assembled in a glove box using metal lithium / sodium / potassium as a counter electrode, and the electrochemical performance was tested.

[0059] The electrochemical performance of each example is shown in Table 1.

[0060] Table 1

[0061]

[0062] Figure 1 The X-ray diffraction pattern (a) and transmission electron microscope patterns (b)-(d) of the porous elemental bismuth obtained in Example 1 are shown. It can be seen that after the treatment in step (1), the porous elemental bismuth was successfully obtained in Example 1, and its nanopores run through the entire interior and surface of the material.

[0063] After freeze-drying and calcination in step (1) and step (2) of Example 1, a two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material was obtained. Figure 2 The X-ray diffraction pattern (a) and the Raman spectrum (b) both confirm the existence of pure metallic Bi phase, and the content of Bi in the material is as high as 93.06wt% ( Figure 2 (c)), which is much higher than the level reported in the current literature.

[0064] Furthermore, transmission electron microscopy revealed that the obtained two-dimensional carbon matrix embedded monodisperse bismuth nanosphere composite material contained ultrafine Bi nanospheres with an average size of 10.23 nm ( Figure 4 ) are completely covered by the two-dimensional carbon matrix, and no exposed Bi nanospheres are found ( Figure 3 (a)-(d) and (g)). Atomic force microscopy scanning revealed that the average thickness of the two-dimensional carbon matrix embedded monodisperse bismuth nanosphere composite material is about 16.42nm ( Figure 3 In (e)-(f), the obvious and continuous step height results in the figure also verify the dense distribution of ultrafine Bi nanospheres in the two-dimensional ultrathin oxygen-rich and nitrogen-doped carbon sheets. Figure 3 Elemental mapping of Bi, C, N, and O elements in (h)–(l) shows that dense Bi is uniformly distributed in the N-doped oxygen-rich carbon sheets.

[0065] This ultra-thin, stable overall two-dimensional structure shortens the path of lithium, sodium, and potassium ions passing through the two-dimensional plane during charging and discharging, ensuring ultra-fast transmission of electrons / ions. The good mechanical properties and good toughness of the two-dimensional structure are conducive to buffering the violent expansion of Bi during the electrochemical reaction, and are conducive to maintaining the structural stability of the material under high-rate and ultra-long cycle cycles. When this material is used in the negative electrode of sodium-ion batteries, it can be used at 50Ag -1 The ultra-high current density provides 397.8 mAh g -1 Ultra-high capacity output, and at 10Ag -1 Under the condition of high current density, after 1600 long cycles, it still maintained 467.3mAh g -1 Excellent capacity, no capacity decay during the cycle ( Figure 5 ). When the material is applied to the negative electrode of potassium ion battery, it can -1 The high current density provides 275.8 mAh g -1 High capacity output, and at 10Ag -1 Under the condition of high current density, the composite material of two-dimensional carbon matrix embedded monodisperse bismuth nanospheres showed excellent electrochemical reversibility and maintained 330.8 mAh g after 1200 cycles. -1 Excellent capacity ( Figure 6 ).

[0066] The present invention provides a preparation method and application of a composite material of two-dimensional carbon matrix sheets embedded with monodisperse bismuth nanoparticles. A new method for synthesizing nanomaterials based on the capillary force of nanopores is adopted. By changing the content of porous elemental bismuth obtained by a liquid reduction method and a carbon matrix precursor, the requirements of ultra-small size, ultra-high content, high-efficiency carbon coating, and adjustable Bi content can be simultaneously achieved to meet the needs of high-performance negative electrode materials for lithium ion batteries and / or sodium ion batteries and / or potassium ion batteries.

[0067] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a composite material of two-dimensional carbon matrix sheets embedded with monodisperse bismuth nanoparticles, characterized in that: The following steps are involved: (1) The bismuth precursor is treated by a liquid reduction method to obtain porous elemental bismuth; (2) dispersing the porous elemental bismuth obtained in step (1) into a system containing a carbon matrix precursor to form a uniform and stable dispersion, and freeze-drying to obtain a hybrid aerogel; (3) calcining the mixed aerogel obtained in step (2) under a protective atmosphere to obtain a two-dimensional carbon matrix sheet-embedded monodisperse bismuth nanosphere composite material.

2. The method for preparing the composite material of two-dimensional carbon matrix sheet embedded with monodisperse bismuth nanoparticles according to claim 1, characterized in that: The bismuth precursor in step (1) is at least one of bismuth oxide, bismuth sulfide, bismuth selenide, bismuth oxybromide, bismuth oxychloride, bismuth oxyiodine, bismuth oxycarbonate, and bismuth selenium oxide; The reducing agent used in the liquid reduction method in step (1) is one of hydrazine hydrate, sodium borohydride and ascorbic acid.

3. The method for preparing the composite material of two-dimensional carbon matrix sheet embedded with monodisperse bismuth nanoparticles according to claim 1, characterized in that: The molar ratio of the bismuth precursor to the reducing agent in step (1) is 0.1-2.5:1; The liquid in the liquid reduction method of step (1) is at least one of water, ethanol and methanol; wherein the ratio of the liquid to the reducing agent is 30-250 mL: 1-10 mmol.

4. The method for preparing the composite material of two-dimensional carbon matrix sheet embedded with monodisperse bismuth nanoparticles according to claim 1, characterized in that: The carbon matrix precursor in step (2) is at least one of graphene, MXene and its derivatives, ammonium citrate, citric acid, chitosan, tartaric acid, gum arabic, cellulose and its derivatives.

5. The method for preparing the composite material of two-dimensional carbon matrix sheet embedded with monodisperse bismuth nanoparticles according to claim 1, characterized in that: In step (2), the mass ratio of the porous elemental bismuth to the carbon matrix precursor is 0.05-10:0.01-5; The ratio of the solvent to the carbon matrix precursor in the dispersion of step (2) is 20-200 mL: 0.01-5 g.

6. The method for preparing the composite material of two-dimensional carbon matrix sheet embedded with monodisperse bismuth nanoparticles according to claim 1, characterized in that: The protective atmosphere in step (3) is at least one of argon and nitrogen; The heating rate of the calcination in step (3) is 1-20°C / min; the calcination temperature is 300-1000°C, and the calcination holding time is 0.5-5h.

7. A composite material of two-dimensional carbon matrix sheets embedded with monodisperse bismuth nanoparticles prepared by the method according to any one of claims 1 to 6.

8. Use of the two-dimensional carbon matrix sheet embedded monodisperse bismuth nanoparticle composite material according to claim 7 in ion batteries.

9. The use according to claim 8, characterized in that: The ion battery includes one of a lithium ion battery, a sodium ion battery, and a potassium ion battery.

10. The use according to claim 8 or 9, characterized in that: The two-dimensional carbon matrix sheet embedded monodisperse bismuth nanoparticle composite material is used as negative electrode material in ion batteries.

Citation Information

Patent Citations

  • Nanometer bismuth / carbon composite material and preparation method thereof

    CN108134090A

  • Nano bismuth composite material, and preparation method and application thereof

    CN113921762A

  • Bismuth composite nanoparticle anodes, methods of making same, and uses thereof

    US20190051898A1

  • Two-dimensional (2D) nanocomposite, preparation method, and use thereof

    US20230035080A1

Cited By

  • Preparation method and application of MXene-Bi ultra-small nanoparticle composite gel electrode material

    CN120695734A